2001
DOI: 10.1002/hbm.1025
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor mapping of the human cerebellum: fMRI evidence of somatotopic organization

Abstract: Functional magnetic resonance imaging (fMRI) was employed to determine areas of activation in the cerebellar cortex in 46 human subjects during a series of motor tasks. To reduce the variance due to differences in individual anatomy, a specific transformational procedure for the cerebellum was introduced. The activation areas for movements of lips, tongue, hands, and feet were determined and found to be sharply confined to lobules and sublobules and their sagittal zones in the rostral and caudal spino-cerebell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
303
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(378 citation statements)
references
References 41 publications
67
303
2
6
Order By: Relevance
“…The orientation of the somatotopic gradient was confirmed with a multivariate linear regression between the digit number associated with a digit patch and the x, y and z coordinates of its centre of mass. The orientation of the somatotopic gradients in lobule V found in this study agrees with those found in previous studies based on motor-task data (Grodd et al, 2001;Wiestler et al, 2011). While Grodd et al did not report an orderly gradient for the individual fingers, they did observe a postero-medial to antero-lateral orientation of the finger representations, along the cerebellar fissures, as was the case in the present study.…”
Section: Lobule Vsupporting
confidence: 92%
See 1 more Smart Citation
“…The orientation of the somatotopic gradient was confirmed with a multivariate linear regression between the digit number associated with a digit patch and the x, y and z coordinates of its centre of mass. The orientation of the somatotopic gradients in lobule V found in this study agrees with those found in previous studies based on motor-task data (Grodd et al, 2001;Wiestler et al, 2011). While Grodd et al did not report an orderly gradient for the individual fingers, they did observe a postero-medial to antero-lateral orientation of the finger representations, along the cerebellar fissures, as was the case in the present study.…”
Section: Lobule Vsupporting
confidence: 92%
“…Testing 4 digits in a motor task, a group study at 1.5 T identified ordered clusters of activation for individual digits in ipsilateral lobule V (Grodd et al, 2001), with the highest activated 10 mm 3 of the xdigits ordered D1 (thumb)-D3-D2-D5 along the posterior-medial to antero-lateral cerebellar fissures. However, the relatively large voxel size used (3 ×3×4 mm) may have hindered the exact definition of finger-specific active regions by effectively averaging over several digits.…”
Section: Introductionmentioning
confidence: 99%
“…These sites were no longer observed in the control study in which motor output was equalized between tasks. In a recent sensorimotor mapping fMRI study of the human cerebellum, Grodd et al (2001) have shown that motor activity of the hand activates ipsi-and contralateral lobule-V at a distance of 15-30 mm from the midline, corresponding with our data. Cerebellar arm areas in lobule-V of the vermis and hemispheres have been identified in monkeys (Middleton and Strick, 1997).…”
Section: Role Of the Distinct Cerebellar Activation Sitessupporting
confidence: 90%
“…Therefore, posterior Crus-I and Crus-II might subserve a dimming detection network. These cerebellar activation sites also did not correspond to the posterior regions involved in hand movement in the mapping experiment of Grodd et al (2001).…”
Section: Role Of the Distinct Cerebellar Activation Sitesmentioning
confidence: 70%
“…However, it has been demonstrated that the posterior cerebellum also possesses a secondary representation of the hand, localized in lobule VIII, while a new sensorimotor representation of the hand produced during complex finger tasks has been mapped to lobule VI (laterally) [Grodd et al, 2001; Rijntjes et al, 1999; Schlerf et al, 2010, 2014]. The current study confirms a widespread involvement of the posterior cerebellum, including lobules VII, VIII, IX and the posterior vermis, all ipsilateral to the hand used, and lobule VI bilaterally associated with the main effect of the visually guided dynamic power grip task used in this study.…”
Section: Discussionmentioning
confidence: 99%